Can the Induction of Labor with Misoprostol Increase Maternal Blood Loss? - Paulo César Praciano Souza; Karla Santana Azevedo Damasceno; Edward Araujo Júnior; Carlos Augusto Alencar Júnior; Francisco Edson de Lucena Feitosa (Revista Brasileira de Ginecologia e Obstetrícia, 2017)
Abstract Purpose To evaluate blood loss during misoprostol-induced vaginal births and during cesarean sections after attempted misoprostol induction. Methods We conducted a prospective observational study in 101 pregnant women indicated for labor induction; pre- and postpartum hemoglobin levels were measured to estimate blood loss during delivery. Labor was induced by administering 25 μg vaginal misoprostol every 6 hours (with a maximum of 6 doses). The control group included 30 patients who spontaneously entered labor, and 30 patients who underwent elective cesarean section. Pre- and postpartum hemoglobin levels were evaluated using the analysis of variance for repeated measurements, showing the effects of time (pre- and postpartum) and of the group (with and withoutmisoprostol administration). Results Therewere significant differences between pre- and postpartum hemoglobin levels (p < 0.0001) with regard to misoprostol-induced vaginal deliveries (1.6 ± 1.4 mg/dL), non-induced vaginal deliveries (1.4 ± 1.0 mg/dL), cesarean sections after attempted misoprostol induction (1.5 ± 1.0 mg/dL), and elective cesarean deliveries (1.8 ± 1.1 mg/dL). However, the differences were proportional between the groups with and without misoprostol administration, for both cesarean (p = 0.6845) and vaginal deliveries (p = 0.2694). Conclusions Labor induction using misoprostol did not affect blood loss during delivery.